2021
DOI: 10.1371/journal.pone.0251745
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association mapping reveals race-specific SNP markers associated with anthracnose resistance in carioca common beans

Abstract: Brazil is the largest consumer of dry edible beans (Phaseolus vulgaris L.) in the world, 70% of consumption is of the carioca variety. Although the variety has high yield, it is susceptible to several diseases, among them, anthracnose (ANT) can lead to losses of up to 100% of production. The most effective strategy to overcome ANT, a disease caused by the fungus Colletotrichum lindemuthianum, is the development of resistant cultivars. For that reason, the selection of carioca genotypes resistant to multiple AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 101 publications
(180 reference statements)
1
8
0
Order By: Relevance
“…A total of 59 MTAs were identified from 09 different GWA studies for anthracnose in common beans ( Figure 4 and Supplementary Table 4 ). Some of the MQTLs were found to be co-localized with MTAs available from more than one GWA study, for instance, MQTL4.1 co-localized with 40 MTAs reported in eight different GWA studies ( Zuiderveen et al, 2016 ; Wu et al, 2017 ; Banoo et al, 2020 ; VazBisneta and Gonçalves-Vidigal, 2020 ; Vidigal Filho et al, 2020 ; Almeida et al, 2021 ; Bisneta et al, 2021 ; Costa et al, 2021 ). Similarly, MQTL1.3 co-localized with 06 MTAs reported in five different GWA studies ( Perseguini et al, 2016 ; Wu et al, 2017 ; Banoo et al, 2020 ; VazBisneta and Gonçalves-Vidigal, 2020 ; Vidigal Filho et al, 2020 ).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…A total of 59 MTAs were identified from 09 different GWA studies for anthracnose in common beans ( Figure 4 and Supplementary Table 4 ). Some of the MQTLs were found to be co-localized with MTAs available from more than one GWA study, for instance, MQTL4.1 co-localized with 40 MTAs reported in eight different GWA studies ( Zuiderveen et al, 2016 ; Wu et al, 2017 ; Banoo et al, 2020 ; VazBisneta and Gonçalves-Vidigal, 2020 ; Vidigal Filho et al, 2020 ; Almeida et al, 2021 ; Bisneta et al, 2021 ; Costa et al, 2021 ). Similarly, MQTL1.3 co-localized with 06 MTAs reported in five different GWA studies ( Perseguini et al, 2016 ; Wu et al, 2017 ; Banoo et al, 2020 ; VazBisneta and Gonçalves-Vidigal, 2020 ; Vidigal Filho et al, 2020 ).…”
Section: Resultsmentioning
confidence: 94%
“…For this purpose, data from 11 different GWA studies on the most stable and significant MTAs/SNPs were collected. These studies included the following: Burt et al (2015) , Perseguini et al (2016) , Zuiderveen et al (2016) , Wu et al (2017) , Fritsche-Neto et al (2019) , Banoo et al (2020) , VazBisneta and Gonçalves-Vidigal, 2020 , Vidigal Filho et al (2020) , Almeida et al (2021) , Bisneta et al (2021) and Costa et al (2021) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has been observed that it is possible to identify materials that are disease-resistant in addition to serving as a basis for signal transduction for plant immune defense [ 55 , 56 ]. The common bean originates from two main gene pools and some diseases [ 8 ], due to the process of coevolution, present the same classification and higher degrees of pathogenicity within specific gene pools [ 9 , 57 ]. These studies indicate that plant photosynthesis and immune defense processes are interconnected [ 58 ].…”
Section: Discussionmentioning
confidence: 99%